Tropical Forest Ecosystem Responses to Increasing Nutrient Availability - Dietrich Hertel (Frontiers Research Topics, 2017)
Deforestation and land use change have led to a strong reduction of tropical forest cover during the last decades. Climate change will amplify the pressure to the remaining refuges in the next years. In addition, tropical regions are facing increasing atmospheric inputs of nutrients, which will have unknown consequences for the structure and functioning of these systems, no matter if they are within protected areas or not. Even remote areas are expected to receive rising amounts of nutrients. The effects of higher rates of atmospheric nutrient deposition on the biological diversity and ecosystem functioning of tropical ecosystems are poorly understood and our knowledge of nutrient fluxes and nutrient limitation in tropical forest ecosystems is still limited. Yet, it will be of paramount importance to know the effects of increased nutrient availability to conserve these ecosystems with their biological and functional diversity. During the last years, research efforts have more and more focused on the understanding of the role of nutrients in tropical ecosystems and several coordinated projects have been established that study the effects of experimental nutrient addition. This Research Topic combines results from experiments and from observational studies with the aim to review and conclude on our current knowledge on the role of additional nutrients in ecosystems.